Conocimientos y prácticas culturales sobre dengue en las familias de un cabildo indígena del departamento de Córdoba (2020)
Introduction: Colombia as a multicultural country generates multiple expressions of health care that are built in different regional contexts, based on the knowledge and practices that are transmitted from generation to generation, originating various forms of prevention and control of vector-transmitted diseases, such as like dengue. Objective: To analyze the knowledge and cultural practices on the prevention and control of dengue in the families of an Indigenous Council of the department of Córdoba. Materials and methods: Qualitative descriptive research with an ethnographic approach; The information collected emphasized the knowledge and cultural practices in 18 families of an Indigenous Council in the department of Córdoba. The data were collected from the application of an interview and participant observation. Results: A basic level of knowledge related to the clinical manifestations of the disease was identified, due to the fact that families recognize dengue as a disease; the predominant risk factor corresponds to the use of buckets, tanks and containers for storing water in the homes and the existence of a road as a means of access to the community. Conclusions: knowledge about dengue in this community is scarce, although there is an acceptable percentage of practices for the prevention and control of the disease, for which it is important that health professionals emphasize education to reduce transmission dengue virus within indigenous communities.